Fathers' evolving role in families whose mothers have emigrated (2021)
This article presents research carried out by the UCPR Family Centre, whose main objective is to offer explanations for situations faced by families in the Colombian coffee region. One of the situations is that of the emigration of women outside the country, which brings about a series of consequences for the families they have created. The article therefore assesses the role of fathers in families whose mothers have migrated abroad and how such emigration produces changes in the role that fathers perform in areas such as communication, authority, affection and family finances. The article is based on semi-structured interviews and focus groups with parents and children of 15 families in the urban area of Pereira and Dosquebradas, as well as seven family units in the urban area of Medellín.